Effect of des-aspartate-angiotensin I on the actions of angiotensin II in the isolated renal and mesenteric vasculature of hypertensive and STZ-induced diabetic rats - Murugan, Dharmani Devi; Mustafa, Mohd Rais; Achike, F.I.; Sim, M.K. (Elsevier, 2005)
The present study investigated the action of des-aspartate-angiotensin I (DAA-I) on the pressor action of angiotensin II in the renal and mesenteric vasculature of WKY, SHR and streptozotocin (STZ)-induced diabetic rats. Angiotensin II-induced a dose-dependent pressor response in the renal vasculature. Compared to the WKY, the pressor response was enhanced in the SHR and reduced in the STZ-induced diabetic rat. DAA-I attenuated the angiotensin II pressor action in renal vasculature of WKY and SHR. The attenuation was observed for DAA-I concentration as low as 10 18 M and was more prominent in SHR. However, the ability of DAA-I to reduce angiotensin II response was lost in the STZ-induced diabetic kidney. Instead, enhancement of angiotensin II pressor response was seen at the lower doses of the octapeptide. The effect of DAA-I was not inhibited by PD123319, an AT2 receptor antagonist, and indomethacin, a cyclo-oxygenase inhibitor in both WKY and SHR, indicating that its action was not mediated by angiotensin AT2 receptor and prostaglandins. The pressor responses to angiotensin II in mesenteric vascular bed were also dose-dependent but smaller in magnitude compared to the renal vasculature. The responses were significantly smaller in SHR but no significant difference was observed between STZ induced diabetic and WKY rat. Similarly, PD123319 and indomethacin had no effect on the action of DAA-I. The findings reiterate a regulatory role for DAA-I in vascular bed of the kidney and mesentery. By being active at circulating level, DAA-I subserves a physiological role. This function appears to be present in animals with diseased state of hypertension and diabetes. It is likely that DAA-I functions are modified to accommodate the ongoing vascular remodeling